Space Transformation Due to Conflict: Changes from Agricultural to Industrial Space in Manyar District, Gresik Regency - Muhammad Mukhobbir Risalah (Institut Teknologi Sepuluh Nopember, 2020)
Changes in the spatial area showed the dynamics of political economy. There is a problem regarding power relations in reproducing space, which will trigger a conflict between interests. These land changes, especially those related to changes in the form of agricultural land use to non-agricultural, have resulted in the loss of income sources for farmers. This paper focuses on the transformation of agricultural land into a non-agricultural one caused by conflict between several elements, including the local government, private businessmen, and the community, especially fishpond farmers who experience marginalization of agricultural land due to industrial development in Gresik Regency. The research is conducted using a qualitative approach with a descriptive type to support more in-depth research in analyzing urban spatial planning issues in the perspective of seeking spatial politics in Gresik district. The current reality is that the government tends to be more aligned with capital owners, which implies that spatial planning is manifested by profit-oriented development, high economic growth, and accumulation. The government mostly ignores ecological and social dimensions, which it considers non-linear with economic investment.